The ultrastructure of the pre-meiotic and meiotic stages of spermatogenesis in Plagioscion squamosissimus (Teleostei, Perciformes, Sciaenidae) - Gusmáo, P. [UNESP]; Foresti, F. [UNESP]; Quagio-Grassiotto, I. [UNESP] (My University, 2002)
Spermatogenesis of 'corvina' P. squamosissimus starts from a stem cell that gives rise to germ cells. These cells are enveloped by Sertoli cells, forming cysts. The germ cells in the cysts are all at the same stage of development and are interconnected by cytoplasmic bridges. Spermatogonia are the largest germ cells. In the cysts, these cells differentiate into primary spermatogonia and secondary spermatogonia. The primary spermatogonia are isolated in the cyst and give rise to the secondary spermatogonia. After several mitotic divisions, they produce spermatocytes I, which can be identified by synaptonemal complexes in the nucleus. The spermatocytes I enter the first phase of meiosis to produce the spermatocytes II. These are not very frequently seen because they rapidly undergo a second phase of meiosis to produce spermatids.
Keywords: Plagioscion squamosissimus; Spermatocytes; Spermatogenesis; Spermatogonia; Teleostei; Ultrastructure; cell differentiation; cell ultrastructure; cytoplasm; germ cell; male; meiosis; mitosis; nonhuman; Sertoli cell; spermatid; spermatocyte; spermatogenesis; spermatogonium; teleost; animal; electron microscopy; Perciformes; physiology; spermatozoon; ultrastructure; Plagioscion; Sciaenidae; Animals; Male; Meiosis; Microscopy, Electron; Spermatozoa